Tilton family papers
Correspondence, military orders, genealogical material, newspaper clippings, photographs, and other papers relating primarily to the Civil War service of the four Tilton brothers. Chiefly letters from Albert Murray Tilton and Robert Antis Tilton who served with the 51st Illinois Infantry Regiment, Henry Tilton, Jr., who served with the 24th New York Light Artillery Regiment, and William Gibbs Tilton who served with the 21st New York Independent Battery to their parents, Henry Tilton, Sr., and Susan Alice Gibbs Tilton, of Moscow, N.Y., describing camp life, movements of the regiments, and details of skirmishes and battles.
Includes descriptions of Albert's service at Corinth, Miss., Chattanooga, Franklin, Missionary Ridge, Nashville, and Stone's River, Tenn., and Atlanta, Chickamauga, and Kennesaw Mountain, Ga.; Henry's service in Newport Barracks, New Bern, and Plymouth, N.C., and his capture and subsequent death at Andersonville prison in 1864; Robert's illness and death of typhoid fever in 1862; and William's service at Morganza, La., and Greenville, Mobile Bay, and Fish River, Ala. Genealogical material includes photographs, obituaries, a biographical sketch of a sister, Mary Anna Tilton, and historical material about the Moscow, N.Y., area.
Family residing in Moscow, N.Y.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Tilton, Albert Murray, -- 1836-1876.; Tilton, Albert Murray, -- 1836-1876 -- Correspondence; Tilton, Henry -- Correspondence; Tilton, Henry, -- 1839-1864.; Tilton, Henry, -- 1839-1864 -- Correspondence; Tilton, Mary Anna; Tilton, Robert Antis, -- 1844-1862.; Tilton, Robert Antis, -- 1844-1862 -- Correspondence; Tilton, Susan Alice Gibbs -- Correspondence; Tilton, William Gibbs; Tilton, William Gibbs -- Correspondence; Tilton family; United States. -- Army. -- Illinois Infantry Regiment, 51st (1861-1865); United States. -- Army. -- New York Artillery. -- Independent Battery, 21st (1862-1865); United States. -- Army. -- New York Light Artillery Regiment, 24th (1862-1865); Andersonville Prison; Alabama -- History -- Civil War, 1861-1865.; Georgia -- History -- Civil War, 1861-1865.; Louisiana -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; North Carolina -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Moscow (N.Y.) -- History